Increasing Purchasing Decision Goals at Ketapang Roast Coffee Through Social Media Interaction - Intan Cahya Wulandari; Parlagutan Silitonga (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
The aim of this study is to determine how price perception and location effects purchase decision and social media interaction. A survey that was delivered to Roast Coffee Ketapang customers using a purposive sample strategy was the research method customer 160 persons were the samples that were taken. The Structural Equation Model is used in the data analysis technique with the use of smart pls 3 software. The findings demonstrate that  price perception and location have a large direct and indirect impact on purchase decision and social media interaction.